الشيخ القاضي شمس الدين بن شير محمد 1901 - 1985 : ومنهجة في التفسير - الحريري، حكمت أحمد (مؤلف), (مجلة الأندلس للعلوم الاجتماعية والتطبيقية, 2023)
الشيخ القاضي شمس الدين بن شير محمد 1901 - 1985 : ومنهجة في التفسير